Design and Implementation of a Structured Programme for Validation of Birth Weights in a District of Southern India: A Case Study - Prem K. Mony, Maryann Washington, Suman Rao, Jayachitra Gajendran, Virgin Thooya, Swaroop N, Arin Kar and Krishnamurthy Jayanna (World Health & Population, 2018)
In India, though the prevalence of low birth weight (LBW) is estimated to be nearly 30%, routine reporting by the government consistently under-reports it as 12%, with resulting mismatched rectification efforts. We designed a programme comprising weight measurement standardization training, a pilot study-based sample size calculation, re-training and certification of personnel and finally a validation exercise. Paired birth weight readings of 404 newborns by a staff nurse and a research nurse were compared. LBW (<2,500 g) prevalence was 18% and 36% according to staff nurse and research nurse, respectively. Thus, it is feasible to set up simple validation exercises.
Keywords: low birth weights, weight measurement standardization, healthcare in India, child health